AN EVALUATING THE IMPACT ON RISING FUEL PRICE ON CONSUMPTION IN BELAGAVI (Journal of Pharmaceutical Negative Results, 2023)
India has surpassed China as the world's third largest importer of crude oil, surpassing it in mid-2020, and imports more than 84% of its oil requirements. India, as one of the world’s largest and fastest-growing energy importers, has relied significantly on crude oil for both energy production and consumption. Historically, rising fuel costs and rising demand for gasoline have been difficult for the general people. This explores activities to discover the sources and effects of escalating charges these days, which are harming the entire financial system, and to provide ways to deal with this externality. This paper attempts to find out the assertive analysis of the effect on fuel price rising in consumption Belagavi city of Karnataka state. The data for the study is collected through Questionnaire with 154 sample sizes of Belagavi people and SPSS is used for analysing the collected data. Finally this research paper which helps to analyse the impact on Rising Fuel Price in Belagavi City proves so and it gives the further researcher to analyse or study over comparison of fuel prices and electrical Vehicles or even public transport system. The analysis found that the increasing fuel price would have a devastating impact on the transportation sector. The government should preserve those sectors which exposed the largest impact from the increasing of the fuel price.